TYPES OF CONJUNCTION (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
In this article, we will talk about the connective (in grammar), a group of auxiliary words that connect sentences and parts of sentences, and we will also comment on the syntactic properties of connectives.
Keywords: Conjunctions, lexemes, singular conjunctions, repeated conjunctions